Methods for checking the goodness of fit of alternative nonlinear mixed models with an application in fertility traits of beef cows - Soto Murillo, Henry W. ([editor no identificado], 1991)
Tesis (Doctor of Philosophy in Animal Sciences)--University of Illinois at Urbana-Champaign, 1991.